Mitigating hiring risks through pre-employment background screening: Methodology based on the personnel security approach - Rushchenko, Julia; Rushchenko, Ihor; Plakhova, Olena (Technium Social Sciences Journal, 2020)
In the wake of the corporate scandals linked to negligent hiring, many organisations worldwide have prioritised background investigations to avoid harm or legal liability and ensure safety of their assets, employees and clients. Negligent hiring takes place when an employer fails to verify that a prospective employee may pose a threat to their company. The article discusses the process of pre-employment screenings aimed at mitigating the risk of corporate fraud, unethical behaviour and organisational deviance. The goal of the article is to analyse a methodological basis for pre-employment background checks carried out by the in-house recruitment experts or third party employee screening companies. A large number of the existing studies have examined the theory and policies of pre-employment screenings, have scrutinised functionality and efficiency of background investigations and have addressed the methods used as part of this process. However, prior research has not identified a comprehensive and integrated technique of carrying out a pre-employment background check. To fill this gap, the paper suggests a vacancy-specific background screening of potential candidates according to the previously defined security criteria formulated in the article. The objective of the abovementioned approach is to generate an effective mechanism of identifying the so-called “risky hires” before the onboarding stage of recruitment. It is argued that both risk evaluation and pre-employment assessments of candidates should be viewed as a standard business practice integrated into a comprehensive hiring corporate policy.